Penyuluhan dan Pemanfaatan Barang Bekas menjadi Ovitrap untuk Mengendalikan Populasi Aedes Aegypti di Langenharjo Grogol Sukoharjo - Setya, Adhi Kumoro; Wahyudi, Didik; Kusuma, Eka Wisnu; Agung, Rendyansah; Widyastuti, Dinda; Valent, Febriana (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Since its first discovery in Indonesia, dengue fever (DHF) has remained a public health threat. Numerous measures have been taken to break the life cycle of its vector, Aedes aegypti, but the number of cases has yet to be eliminated. The disease seems to spread randomly, and its incidence is unpredictable. Often, outbreaks are accompanied by fatalities. Research into environmentally friendly and safe materials has been extensively conducted, but this disease has not yet been effectively eradicated. To maximize the prevention and elimination of dengue fever, it is crucial to understand the behavior of the vector to achieve accurate and optimal results. The primary objective of this activity is to prevent dengue fever, as several cases of dengue fever were reported in Grogol district earlier this year. This activity was held in May 2024 in Langenharjo sub-district, Sukoharjo city, with 47 participants. After participating, community understanding increased, as reflected in the average score of 89.79. Participants and cadres can carry out and socialize effective dengue fever prevention and are able to prevent and eliminate dengue fever using the ovitrap technique.